Influence of some structural characteristics of the ionic liquids on homogeneous and heterogeneous characteristics of their mixtures with water and alcohols. - S. A. Reshetov; A. K. Frolkova; A. A. Muzyka (Тонкие химические технологии, 2009)
The article presents a study of influence of the structural characteristics of ionic liquids, such as length of alkyl chain of the cation, cation's symmetry, type of the cation, type of the anion and some others, on the homogeneous and heterogeneous characteristics of the mixtures of ionic liquids with water and alcohol.